American Indian community engagement and the structural and social determinants of health: results from the THRIVE assessment - Webb, Kellie; Posey, Sadie; Hirchak, Katherine; Beamon, Emily; Milligan, Kelley; Wagon, Sharon; Fatupaito, Bethany; Kelley, Allyson (Frontiers in Public Health, 2025)
IntroductionEngaging community members in the process of documenting health inequities is the first step in addressing public health challenges. This paper presents the community-driven adaptation process and results for the Tool for Health and Resilience in Vulnerable Environments (THRIVE) assessment, a social justice and equity-focused screening tool, in one reservation-based American Indian community in the US.MethodsUsing principles of community-engaged research (CER) and community-based participatory research (CBPR), the authors describe the importance of co-creating data collection tools with community members to document the social and structural determinants of health. Authors describe a step-by-step approach to document inequities; this includes (1) recognizing the need to document inequities, (2) identifying existing tools to measure inequities, (3) adapting tools and piloting them with members of the community, (4) refining the tool based on community feedback, and (5) administering the tool to address needs identified.ResultsSurvey data from the THRIVE assessment and community-engaged process (N = 100) documented the social and structural determinants of health. The community-adapted THRIVE assessment examined the underlying factors of people, places, and opportunities that contribute to health inequities in the community. Results from this work show that the adapted THRIVE tool has high psychometric reliability (α = 0.957) and that community members feel strong about factors related to people and vulnerability, as well as factors related to place and equitable opportunities. The authors discuss future work and actions they will undertake to address community-identified concerns through community-based programs like complementary alternative medicine, harm reduction via mobile outreach, employment readiness and job training, sober housing, culturally centered treatment, and voucher-based programs to meet basic needs. The process presented underscores the importance of involving American Indian community members in co-creating data collection tools that represent the community’s needs and interests. This intersectional, holistic approach aims to enhance community conditions and achieve the highest possible health and well-being for American Indian communities.